METHODOLOGY OF THE ENTERPRISE ADAPTATION STRATEGY DETERMINING - Victoria Grosul; Timur Askerov (Izdevnieciba "Baltija Publishing", 2019)
This research paper reveals the step-by-step method of retail enterprises strategy adaptation determining. Alternatives of retail enterprise strategic goals achieving are substantiated in terms of adaptation to environmental factors effect for of retail trade enterprises, the purpose of which is survival; for enterprises that are interested in providing their sustainable position in the market; for enterprises that activities are focused on providing effective business development in the strategic perspective. Account that the critical limit of enterprise adaptive development corresponds to enterprise's strategic goal - survival providing under determining alternatives for retail enterprise strategic goals achieving in terms of adaptation to environmental factors. The main content characteristics of adaptation strategy main types are highlighted on the base of basics theory and methodology of enterprise adaptation strategic management generalization: preventive adaptation strategy, moderately preventive adaptation strategy, active adaptation strategy, moderately active adaptation strategy, passive adaptation strategy, moderately passive adaptation strategy. Trajectory concept was taken into account under retail enterprise adaptive potential level determining. Comprehensive assessment of adaptation potential was carried out according to the criteria of flexibility, mobility and stability. This assessment allows determining the enterprise readiness to successful implementation of adaptation strategy under dynamic changes, as well as assessing the effect degree of adaptation properties on the overall level of enterprise stability. The models' set is proposed for adaptation level of retail enterprise to the environmental factors action assessment. The "strategic adaptation space" matrix is proposed for enterprise adaptation strategy choice; it creates opportunity to combine the enterprise adaptive potential assessment and takes into account its ability to environmental factors action adapting. Retail enterprises positioning in the matrix field, according to adaptation potential assessment indices values and retail enterprise adaptation level to environmental factors action allows determining the optimal type of adaptation strategy for retail enterprises.